Duret Hemorrhage after Extradural Hematoma Evacuation–A Rare Entity - Tyngkan, Lamkordor; Mahfouz, Nazia; Bilal, Sobia; Fatima, Bazla; Malik, Nayil (Indian Journal of Neurotrauma, 2021)
Traumatic brainstem injury can be classified as primary or secondary. Secondary brainstem hemorrhage that evolves from raised intracranial pressure (ICP) and transtentorial herniation is referred to as Duret hemorrhage. We report a 25-year-old male who underwent emergency craniotomy, with evacuation of acute epidural hematoma, and postoperatively developed fatal Duret hemorrhage. Duret hemorrhage after acute epidural hematoma (EDH) evacuation is a very rare complication and the outcome is grave in most of the cases.
Keywords: Epidural hematoma; extradural hematoma; Duret hemorrhage; craniotomy; postoperative complications